HELMINTHIC ASSEMBLAGES OF SERIOLELLA POROSA GUICHENOT 1848 (PISCES: CENTROLOPHIDAE) FROM SAN MATÍAS GULF (ARGENTINA) - Guagliardo, Silvia (2014)
No previous studies were carried out on aspects of the helminth assemblages of Seriolella porosa. The present study aims to analyze the metazoan parasite of S. porosa and establish the relationship between the parasitic variations and both fish size and sex. A total of 101 specimens of S. porosa from San Matías Gulf, Argentina were examined between September and October 2006. Thirteen species were reported with a total of 3366 parasites. Lecithocladium cristatum was the most prevalent, dominant and abundant species. The average species richness was 3.2 ± 1.20. The evenness showed an inverse correlation with the total number of parasites and did not reveal differences between host sexes. None of the parasite species showed interspecific associations with each other. The average richness of the infracommunity was significantly less than the component community. The helminth community of the silver warehou shows little diversity with many satellite species and only two core species (Anisakis sp. and L. cristatum). Further studies, using parasites as stock indicators, would indicate whether the San Matías population represents a reproductive aggregation that penetrates the gulf seasonally in winter or whether it is a permanent stock isolated from the continental shelf.